Household food security and diet quality with chronic energy deficiency among preconception women - Pradita Putri Ramadhani; Fillah Fithra Dieny; Dewi Kurniawati; Hartanti Sandi; Deny Yudi Fitranti; Ayu Rahadiyanti; A. Fahmy Arif Tsani (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
Background: Chronic energy deficiency (CED) that occurs at risk preconception women during pregnancy increased low birth weight (LBW) in infants. Household food security and diet quality are factors that cause CED. Therefore, this study aims to determine the relationship between household food security and diet quality with CED preconception women.Materials and Methods: We used a cross-sectional study design. The subject of 70 preconception women aged 16-35 years registered in the religious affairs office in Sumowono and Pringapus Subdistrict were selected by consecutive sampling method. Weight and height were measured to assess body mass index to determine CED. Household food security was measured using the Household Food Security Scale Module (HFSSM). Food intake data were obtained using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) and DQI-I (Diet Quality Index-International) to measure diet quality. Bivariate analyses were tested using Rank Spearman and Pearson Product Moment.Results: The prevalence of subjects with CED risk was 48.6% and subjects with CED was 15.7%. 38.6% of subjects married at the age of 16-20 years, 75.1% of subjects had low household food security and 80% of subjects had low diet quality. There was no significant relationship between household food security and diet quality with CED, namely (p = 0.537) and (p = 0.711). The components of diet quality, namely variation, adequacy, moderation and balance also did not show a significant relationship with CED, respectively with p-value (p = 0.711), (p = 0.523), (p = 0.412), (p = 0.604 )Conclusions: There was no correlation between household food security and CED, also no correlation between diet quality and CED.